2011
DOI: 10.1016/s0959-8049(11)70166-6
|View full text |Cite
|
Sign up to set email alerts
|

Experimental models for the development of new medical treatments in prostate cancer

Abstract: Although prostate cancer is a major cause of death and morbidity in western countries, one major obstacle in the progress of prostate cancer studies has been the limited number of relevant preclinical models. Even so, these models constitute the major preclinical tool required for the further development of new therapeutic strategies. Nevertheless, current limitations have hampered the transition of scientific findings from these models to human clinical trials. Each xenograft and genetically engineered mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 88 publications
2
9
0
Order By: Relevance
“…We have recently generated a CRE‐inducible PIM1 transgene and have used this model to express the kinase in the prostate tissue (Narlik‐Grassow et al, data not shown). We have found that increased expression of PIM1 alone or in combination with the loss of one Pten allele was not sufficient to produce full‐blown adenocarcinoma, but was definitely a factor in the increased severity of prostatic neoplasias, as reported with other models . These results are in agreement with data from PIM1 overexpression studies in prostate cell lines, which showed that PIM1 overexpression alone was not sufficient to transform benign cells to malignancy, but could enhance, both in vitro and in vivo, the tumorigenic capabilities of tumor cells .…”
Section: Pim Kinases As Carcinogenesis Promoting Genessupporting
confidence: 90%
See 1 more Smart Citation
“…We have recently generated a CRE‐inducible PIM1 transgene and have used this model to express the kinase in the prostate tissue (Narlik‐Grassow et al, data not shown). We have found that increased expression of PIM1 alone or in combination with the loss of one Pten allele was not sufficient to produce full‐blown adenocarcinoma, but was definitely a factor in the increased severity of prostatic neoplasias, as reported with other models . These results are in agreement with data from PIM1 overexpression studies in prostate cell lines, which showed that PIM1 overexpression alone was not sufficient to transform benign cells to malignancy, but could enhance, both in vitro and in vivo, the tumorigenic capabilities of tumor cells .…”
Section: Pim Kinases As Carcinogenesis Promoting Genessupporting
confidence: 90%
“…We have found that increased expression of PIM1 alone or in combination with the loss of one Pten allele was not sufficient to produce full-blown adenocarcinoma, but was definitely a factor in the increased severity of prostatic neoplasias, as reported with other models. 67,68 These results are in agreement with data from PIM1 overexpression studies in prostate cell lines, which showed that PIM1 overexpression alone was not sufficient to transform benign cells to malignancy, but could enhance, both in vitro and in vivo, the tumorigenic capabilities of tumor cells. 69,70 For example, the expression of PIM1 in human prostate cell lines that represented different stages of the disease showed that PIM1 overexpression alone was not sufficient to transform benign RWPEI cells to malignancy, but it could enhance the tumorigenic capabilities of LNCaP and Du145 69 or PC3 prostate tumor cells, both in vitro and in vivo.…”
Section: Pim Kinases As Carcinogenesis Promoting Genessupporting
confidence: 88%
“…Despite recent advances in diagnosis and treatment of this disease, it still considerably accounts for cancer‐associated morbidity and mortality, especially in the elderly. To further advance the transfer of scientific findings from the laboratory to the patient, reliable, and representative preclinical model systems are needed . Here, the technique of orthotopic xenografts constituted a major step forward.…”
Section: Introductionmentioning
confidence: 99%
“…To further advance the transfer of scientific findings from the laboratory to the patient, reliable, and representative preclinical model systems are needed. 5,6 Here, the technique of orthotopic xenografts constituted a major step forward. These comprise diverse innovative, increasingly used in vivo models to study human PCa, in which cultivated human PCa cells, or intact human PCa tissue pieces are implanted into the prostate of immunodeficient mice.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer (PCa) is the most common cancer in men and has a high morbidity and mortality . Despite this, PCa research is still hampered by the limitations of current preclinical models in vitro and in vivo . Especially in vivo models fail to display intraprostatic growth of PCa and therefore the ability to mimic natural tumor growth behavior and characteristics .…”
Section: Introductionmentioning
confidence: 99%